Komparasi Efektivitas Biaya Pelatihan Sumber Daya Manusia Pada Bank Umum Syariah di Indonesia - Nurati Nurati; Retno Kusumastuti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Training is essentially a learning process. Maqashid sharia as the foundation of sharia banking has the first goal of educating or conducting research for individuals. Industry competitiveness will not be able to increase without employees who are reliable and competent in their fields. The industry invests heavily in the training and development of its employees. It is time for the organization or BUS to change their perspective on aspects of employees in the organization or BUS, if they want BUS or their organization to be superior and bigger. This study aims to analyze the cost-effectiveness of BUS training in Indonesia in the period 2020 to 2022. The method used is descriptive analysis with a comparative model and quadrant analysis between sampling on the performance of the training cost-effectiveness ratio. The results of the study used quadrant analysis, namely BUS in quadrant 1: PT BPD Nusa Tenggara Barat Syariah (NTBS), PT. Bank Muamalat Indonesia (BMI), PT. Bank Aceh Syariah (BACS) and PT. Bank Victoria Syariah (BVIS). Quadrant 2 namely: PT. Bank Jabar Banten Syariah (BJBS), PT. BCA Syariah (BCAS) and PT. Bank Syariah Indonesia, Tbk (BSI). Quadrant 3 is nil. Finally in quadrant 4 there are: PT. Bank Mega Syariah (BMS), PT. Bank Panin Dubai Syariah, Tbk (BPDS), PT. Sharia National Pension Savings Bank, Tbk (BTPS), PT. Bukopin Sharia Bank (BSB) and PT. Bank Aladin Syariah, Tbk (BAL). Categorization using quadrant analysis indicates that the BUS industry in Indonesia is mostly not effective in managing and realizing HR training costs. Keywords: Training, human resources, Islamic banking